Pelatihan Canva untuk Mendukung Optimalisasi Media Pembelajaran Berbasis Teknologi Informasi dan Komunikasi (TIK) - Putu Gede Surya Cipta Nugraha; I Made Anom Mahartha Dinata; I Putu Dody Suarnatha; Ni Ketut Gita Saraswati; I Putu Gede Buda Mardiksa Putra (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2026)
At the primary school level, integrating ICT-based learning media is crucial; it not only expands access to learning resources but also fosters digital literacy among students from an early age. The partner for this initiative is Adi Widyalaya Gurukula Bangli Primary School. While teachers there already utilize digital devices to support the learning process, their usage remains largely limited to existing internet materials, videos from sharing platforms, or simple presentations. Such practices indicate that technology integration is still at a basic adoption stage and has not yet fully evolved toward creating more contextual and interactive learning media. This activity aims to enhance teachers' understanding of ICT-based learning media, their proficiency with the Canva application, their skills in designing and developing learning media, and their ability to utilize Canva AI. The implementation method employs a participatory training approach combined with hands-on guidance in creating Canva-based learning media. The results demonstrate that the training successfully strengthened the teachers' knowledge, skills, and readiness to use Canva as an ICT-based learning tool. Teacher acceptance of Canva was also high, as the application is considered user-friendly, engaging, and relevant for developing teaching materials.